Understanding the pathogenesis and potential therapeutics of Myotonic dystrophy - Verma, Ayushri (2024)
Myotonic dystrophy is the most common type of muscular dystrophy, a genetic condition that is known for causing the muscles to progressively weaken. Other clinical symptoms include prolonged muscle contractions, cataract, diabetes, cardiac defects, respiration issues, and more. The clinical variability, multi-system involvement and increasing severity of symptoms with generations of the disease makes it complex to cure. There are two types of myotonic dystrophy, type 1 and type 2, both of which result from expanded repeat mutations leading to similar molecular pathogenic pathways. The genetic mutation results in expansion containing DMPK RNA which accumulate and interfere with essential cellular processes. The accumulating RNAs appear in the form of foci in the nucleus of the cell, when visualised with in situ hybridization using a fluorescently labelled probe. This study sets out to test and examine the effects of macrolide rapamycin, CDK12 inhibitors and protein phosphatases on quantity of foci and understand the molecular pathogenies of the disorder. In order to test the compounds/therapeutics, immunofluorescence, western blotting, PCR and genome editing using CRISPR Cas9 were some of the techniques used on the patient generated immortalized human KB-TeloMyoD (DM1) fibroblasts, KAGO-TeloMyoD (DM2) fibroblasts. The presence of foci in the DM fibroblasts and the apparent absence of foci in the control/unaffected cells were a definitive indication of genetic mutation and pathology of the disorder. Rapamycin, a macrolide compound was tested in both type 1 and type 2 mutant fibroblasts to determine its effect on the presence of foci. A significant reduction in the quantity of foci was observed in both type 1 and type 2 mutant cells. Further, CDK12 inhibitors, Dinaciclib and 8081 considered as potential therapeutics were tested on HSALR mouse disease models. Dinaciclib produced a slight reduction in foci clusters, however, 8081 didn’t show any reduction. Lastly, genome editing using CRISPR Cas9 targeting the catalytic subunits of previously studied protein phosphatase PP1 was conducted to examine its outcome on the foci and DNA mutation. It was observed that even though we observed no evidence of genome editing in any of the catalytic subunits, a slight decrease in the foci was observed in case of PP1CA and PP1CB.